Typical American Farm at Firestone Factory and Exhibition Building, New York World's Fair (Firestone Tire & Rubber Co.)
Dropped into a modernistic, whirling "World of Tomorrow," in a peaceful, quiet, typical American farm setting, complete with babbling brook, farm building and domestic animals is an interesting and instructive display of modern farming equipment. Here you may see how the Firestone Ground Grip Tire for tractors and farm implements has revolutionized agriculture to make the farmer's work easier, more efficient and more profitable. Firestone Put the Farm on Rubber